Making assessment matter : using test results to differentiate reading instruction - Lesaux, Nonie K.; Marietta, Sky H.. (New York : Guilford Press, 2012)
' All too often, literacy assessments are given only for accountability purposes and fail to be seen as valuable resources for planning and differentiating instruction. This clear, concise book shows K-5 educators how to implement a comprehensive, balanced assessment battery that integrates accountability concerns with data-driven instruction. Teachers learn to use different types of test scores to understand and address students' specific learning needs. The book features an in-depth case example of a diverse elementary school that serves many struggling readers and English language learners. Reproducible planning and progress-monitoring forms can be downloaded and printed in a convenient 8 1/2' x 11' size.'--Provided by publisher.
Machine generated contents note: I. Foundational Issues for Data-Driven Instruction 1. A New Relationship with Student Data2. Why Many Readers Fail3. An Assessment Battery That WorksII. Assessment Considerations for Special Populations4. Assessment to Support Struggling Readers5. Considerations for Linguistically Diverse StudentsIII. Action Steps for Improved Instruction6. Identifying Instructional Priorities and Designing Effective Instruction7. Putting Schoolwide Response to Intervention in Place8. Leading Data-Driven Instruction.
Includes bibliographical references and index.
Keywords: Reading -- Remedial teaching; Reading (Elementary); Reading -- Ability testing; Educational tests and measurements; Individualized instruction; Learning disabled children; Response to intervention (Learning disabled children)